Islamic schooling in the Russian Federation in the context of Muslims’ basic rights and social justice - Akhmetova, Elmira (2019)
This paper aims at reviewing the status of Islamic schooling in the Russian Federation (RF) within the framework of Muslims’ basic rights and social justice. The paper argues that, although Muslims constitute at least 14% of the total population (14-20 million out of 142 million of the total population) and are indigenous to Russia, they are deprived from the rights for establishing the efficient Islamic schooling structure for Muslim kids due to the absence of social justice, and the rise of Islamophobia, especially after 9/11. The first part of the paper discusses the status of religious education at Russian public schools in general. The 1997 law on religious freedom establishes the secular nature of public school education in Russia, although a course in “Fundamentals of Orthodox Culture” is part of the syllabus from 2002. Since 2012, pupils are offered the choice of studying Russia’s four federally recognised religions – Russian Orthodoxy, Islam, Buddhism and Judaism – as well as a course in comparative religions. The paper suggests that such dissection of pupils based on their religious identities may instigate social disintegration and the sense of antipathy among the classmates. The subsequent part of the paper focuses on the reality of Islamic schools in Russia. Exclusive of the North Caucasus region, only few private primary and secondary Islamic schools managed to survive in the central parts of contemporary Russia due to the registration restrictions and state accreditation issues. In addition to all the compulsory secular subjects listed in state school curriculum, the pupils at these Islamic schools also study Arabic, the Qur’an recitation, the basics of fiqh and ‘aqidah. Muslim children who do not have the option of attending Islamic schools may get basic knowledge about Islam at Sunday schools in mosques in the cities and some villages although such facilities are not everywhere obtainable or could not always satisfy the children’s interest. The absence of the proper curriculum and textbooks is another issue that deepens the crisis. The last part of the paper discusses the issues related to well-being of Muslim pupils at Russian public schools, such as the bullying, discriminations, the rights of Muslim girls to wear hijab, Islamophobia, and the access to halal food. Since 2016, the cases of head scarf-wearing Muslim school-girls being prevented from entering schools and universities, and various types of discrimination against and harassment of Muslim girls by school authorities were recorded in many Russian cities. Various public polls reveal that more than 80% of Russian public oppose having religious diet (halal food) and symbols (hijab) in public schools. Due to such public hatred towards Islam and social injustices prevailing in public schools, some Muslim parents are obliged to opt for home schooling thus consequently deepening the social gap and public disintegration among various religious communities in Russia. Lastly, the paper encourages the Russian state and its Muslim community to establish the right system of Islamic schooling for Muslim children in line with the basic human rights for education, religious freedom, human dignity and wellbeing of multicultural Russian society.